Bacterial profile, treatment outcomes, and determinants among adult patients with musculoskeletal infections admitted to Jimma Medical Center: A prospective observational study - Desalegn Gizaw; Gorfineh Teshome; Kisi Chemeda; Aster Wakjira; Mekonnen Damessa (PLoS ONE, 2025)
Background The epidemiological characteristics of musculoskeletal infections are constantly evolving. Despite the significant burden of musculoskeletal infections in sub-Saharan Africa, there is a scarcity of data regarding the potential causes and treatment outcomes of such infections in the region. Therefore, the primary objective of this study was to assess a management protocol, clinical outcomes, and associated factors among adult individuals diagnosed with musculoskeletal infections. Methods Adult patients admitted to Jimma University Medical Center (JUMC), Ethiopia with a diagnosis of musculoskeletal infections was enrolled prospectively from July 2022-December 2022. Clinical characteristics, management protocol, and complications were recorded from admission to discharge. Bacteria were identified by a series of biochemical tests, and antimicrobial susceptibility testing was performed using the Kirby-Bauer Disk diffusion method. Data were analyzed by using SPSS v.23 and the p-value <0.05 was considered statistically significant. Result Among 160 participants included in the study, 103(64.37%) were male, and the mean age 33.51 ± 13.56 years. About 94 (58.8%) of patients had microbial growth, of which 75.5% accounts for mono-microbial. The common bacterial isolates were Staphylococcus aureus in (22.4%), Escherichia coli (18.1%), Pseudomonas aeruginosa (14.7) and Klebsiella pneumonia (11.2). The isolated etiologies were resistant to Ceftriaxone in 67(81.70%) and Ceftazidime in 47(61.8%) of test results. Nearly all (98.8%) of patients were took antibiotics on admission and Ceftriaxone was highly utilized as monotherapy in (23.4%) of patients. Nearly half (46.9%) of the patients were develop treatment failure. Sex [AOR = 2.56, 95%CI (1.07–6.23)], microbial growth [AOR = 3.03, 95%CI (1.31–6.97)], ceftriaxone resistance [AOR = 4.46, 95%CI (1.06–18.67)], co-morbidities [AOR = 2.32, 95%CI (1.007–5.36)], and complications [AOR = 2.80, 95%CI (1.26–6.20)] were associated with treatment failure outcome. Conclusion Close to half of adult patients with musculoskeletal infections experienced treatment failure. Staphylococcus aureus stood out as the prevailing bacterial strain identified. The timely switching of parenteral antibiotics to oral counterparts, alongside timely surgical interventions, significantly enhanced the recovery outcomes for these individuals.